Analisis Perubahan Tutupan Lahan di Kecamatan Pangururan Kabupaten Samosir Menggunakan Sistem Informasi Geografis - Hanna Prillysca Chernovita; Marasi Golfrit Silalahi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Land cover changes in Pangururan District, Samosir Regency, are a significant phenomenon due to population growth and development. This study aims to analyze land cover changes over the period 2018-2022 using Geographic Information System (GIS) technology and Sentinel-2 satellite imagery. The analysis was conducted using the overlay method to compare land cover maps from two different time periods. The results indicate an increase in agricultural land and built-up areas, along with a decrease in shrubland. These changes have impacted the environment and local communities, including erosion potential, declining soil quality, and urbanization. This study is expected to provide insights for sustainable land management in Samosir Regency.